Examining Factors Influencing Students’ Satisfaction and Engagement with Flipped Classroom in Private Universities in Zhaoqing, Guangdong Province, China - Guan, Yibo (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
This research paper aims to investigate the factors influencing student satisfaction and engagement in the use of flipped classroom in private universities in Zhaoqing, Guangdong Province. The conceptual framework proposes a causal relationship between perceived quality, perceived value, student interactions, teaching process, instructional content, student satisfaction, and student engagement. The researcher used a structured questionnaire distributed to 500 students from Zhaoqing, Guangdong Province, including first-year students, sophomores, and juniors. Structural equation modeling and confirmatory factor analysis were used to analyze the data, including model matching, reliability, and structure validation. The results of the analysis showed that perceived quality, perceived value, teaching process, and student interaction had a significant effect on student satisfaction. Student satisfaction has a very strong positive and significant impact on student engagement, while educational content had little effect on the usage of flipped classroom by the students. Through structural equation model data analysis, it was found that the teaching process has the greatest impact on student satisfaction and involvement in the flipped classroom, as well as subsequent interaction with the students, value, and perceived quality. Six of the seven hypotheses have been accepted. Therefore, it is recommended that the management team and teachers of private universities provide assessments to measure the development plan of the flipped classroom teaching model of the influencers to learn engagement.